Quantitative and qualitative analysis of goat's milk antibiofilm against Streptococcus mutans and Candida albicans: an experimental study - Chismirina, Santi; Vernanda, Evlin; Dericco, Deffan; Sungkar, Suzanna; Rezeki, Sri; Said, Shahida Mohd (Padjadjaran Journal of Dentistry, 2025)
Introduction: Streptococcus mutans and Candida albicans interact in dental plaque biofilm to form a synergistic caries process. As a result, preventing tooth cavities necessitates disrupting the interaction between these two bacteria. This can be accomplished by giving anti-biofilm substances such as goat's milk, which contains lactoferrin, lactoperoxidase, and lysozyme. Candida albicans in dental biofilms promotes more violent caries than biofilms generated only by Streptococcus mutants. This study aimed to analyze the antibiofilm of goat's milk against Streptococcus mutans and Candida albicans biofilm masses quantitatively and qualitatively. Methods: The type of study used was an experimental laboratory with a Post-Test Control Group Design. The study was conducted utilizing the Biofilm Coverage Rate (BCR) and the Biofilm Assay to asses characteristics of the quantitative concentration of biofilm and the SDS-PAGE technique to observe the biofilm protein composition qualitatively. Results: The treatment group's BCR and Biofilm Assay concentrations were 0.45 ± 0.2 lower than the negative control group's 0.78 ± 0.25. Protein profile bands of S. mutans and C. albicans biofilms exposed to goat's milk ranged from 14.4 to 116 kDa. Conclusion: Goat milk exhibits anti-biofilm action against Streptococcus mutans and Candida albicans biofilms.